The genus Tenuipalpus (Acari: Tenuipalpidae) in Greece - Hatzinikolis, Ε.Ν. (ENTOMOLOGIA HELLENICA, 1986)
Knowledge of the Greek mites of the genus Tenuipaipus was limited to the following two species only: T. caudatus (Doges) and T. granati Sayed. Recent studies revealed the presence of another five species namely: T. crassus Andre, T. pacificus Baker, T. punicae Pritchard and Baker, T. rosae Kadzhava and T. zhizhilashviliae Reek. A key to the seven species now recorded from Greece is presented. Some information concerning the distribution, economic importance and host plants of the above mentioned Tenuipalpus species is also given.